Citing literature in biomedical research: Citing literature - Pavlovic, Vedrana (Medicinski podmladak, 2021)
Abstract Even though it is considered to be the least demanding part while writing a paper, significant attention should be devoted to citing literature. By using citation, original authors are acknowledged, readers are directed to the used material, validity of the used sources is confirmed, evidence of current research is provided, and plagiarism is avoided.  Numerous shortcomings in the citation of scientific literature have been recognized in recent times. Results of a recent meta-analysis showed that 25.4% of published scientific papers consisted of citation errors. The academic community encounters the problems of incorrect citations on a daily basis, and assessing the accuracy of citations requires considerable effort. Most researchers are aware of the presence of various citation errors, but few respect their presence, ie. the consequences of the identified problem. Assessing the presence and type of inaccurate citations in the biomedical scientific literature, as well as identifying factors associated with their presence, is important for preserving the integrity of the academic community. To improve citation accuracy in the biomedical scientific literature, recommendations for authors, mentors, readers and editors should be implemented in academic environment. These recommendations would encourage good citation practice, prevent errors and promote progress throughout the scientific community. Key words: Citation, Biomedical literature, Accuracy
Keywords: Citation; Biomedical literature; Accuracy